Exploring Greek Primary Teachers’ Perspectives in Inclusive Education for Special Educational Needs (SEN) Students and Related Research Trends: A Systematic Literature Review - Georgia Sakellaropoulou; Natalia Spyropoulou; Achilles Kameas (Education Sciences, 2025)
Inclusive Education aims to ensure equitable learning opportunities for all students, including those with special educational needs (SEN) and disabilities, by promoting accessible teaching practices and supportive learning environments. Although its importance for fostering the academic and social development of diverse learners has been widely recognized in international policy and research, its practical implementation is still under investigation, particularly within the Greek primary education system. This study investigates (a) Greek primary school teachers’ perspectives, focusing on their attitudes, knowledge, challenges, and perceived needs in Inclusive Education for SEN students and (b) research trends relating to these perspectives, focusing on publication trends and methodological characteristics, through a systematic literature review using the PRISMA methodology. The analysis revealed a shift in Greek primary teachers’ attitudes towards Inclusive Education for SEN students, trending towards neutral or negative responses, alongside limited knowledge, various challenges, and an absence of targeted support mechanisms. The analysis also highlighted chronological gaps between the identified studies in international journals and a variability in methodological approaches and sample characteristics. These insights point to a pressing need for further targeted and ongoing research on Greek primary teachers’ perspectives and professional development initiatives to enable effective and inclusive practices for SEN students in Greek primary education.